Lung cancer in lifelong non-smokers. Edinburgh Lung Cancer Group. Issue 8 (August 1991) - Capewell, S; Sankaran, R; Lamb, D; McIntyre, M; Sudlow, M F
Abstract : The Edinburgh Lung Cancer Group registered 3070 new patients with lung cancer in the five years 1981-5 from a catchment population of 950, 000. After review only 74 (2%) were classified as lifelong non-smokers. They differed significantly from the 2996 smokers with lung cancer in that far more were female (77% v 26%) and their mean age was higher (75.4 v 68.0 years). More were in the worst Karnofsky performance categories and fewer patients underwent surgery. The stages of disease were similarly distributed in the two groups and the five year survival was equally poor (5%). Histological cell type was determined in 59 of the 74 patients. All histological cell types were present. More non-smokers had adenocarcinoma than smokers (42% v 13%) and fewer had squamous cell carcinoma (32% v 49%) or small cell carcinoma (15% v 24%). Lung cancer in lifelong non-smokers is uncommon and the diagnosis should therefore always be questioned.